Potential threat of avian influenza to Ethiopian export trade: A review of available literature - Dessie, Tadelle; Kassa, T.; Jobre, Y. (2005)
In this review paper, available information on Avian Influenza Virus (AIV) in relation to its history, pathogenicity, distribution, economic importance, the growing public health concern and the an emerging trade-sensitiveness of the disease caused by the virus on the faces of recently reported outbreaks in the world and its implications to Ethiopia is presented. Finally, recommendations are made in view of the prevailing local and global facts and specific consideration of the situations in Ethiopia with reference to the threat of AIV and the need to develop disease surveillance capabilities and developing information collection and dissemination platforms.